Translation as the site of lexical creation and analysis: Internationalisms in the historical queer lexicon - Lo Vecchio, Nicholas (Meta, 2024)
Understood broadly as a kind of language contact, translation plays a considerable role both in the construction of internationalized lexis and in our study of it. Translations are often the site of the earliest attested or pivotal use of interlingual lexical transfers (“loanwords”); in the most radical case, actual lexical creation originates within translational practice itself. Renée Balibar’s notion of colingualism offers a compelling alternative to borrowing and translanguaging as a way of explaining internationalisms. Case studies on internationalisms coined in the late nineteenth century (sodomy as ‘bestiality’, sapphism, uranism/uranist) exemplify a lexicological approach to translation analysis that focuses on explaining how the lexical types found in specific translations relate to the larger internal lexical structure of a language. The semantic field of historical queerness is only an example: the translational analytical approach demonstrated here can be applied to the lexicological study of any vocabulary informed by language contact.